2009
DOI: 10.1242/dev.027920
|View full text |Cite
|
Sign up to set email alerts
|

Target recognition at the tips of postsynaptic filopodia: accumulation and function of Capricious

Abstract: While much evidence suggests that postsynaptic dynamism contributes to the formation of synapses, few studies have addressed its possible role in target selection. Do postsynaptic motile structures seek specific synaptic partner cells, as does the presynaptic growth cone? Here we studied the dynamics of myopodia, postsynaptic filopodia in Drosophila muscles, and the role of Capricious (CAPS) during the process of synaptic matchmaking. CAPS is a target recognition molecule with an extracellular domain containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 39 publications
3
47
0
2
Order By: Relevance
“…Hbs might be preferentially localized at the protrusions of pLPCs that interact with R axons. The behavior of pLPCs is analogous to 3311 RESEARCH ARTICLE Hibris/Roughest in retinotopic mapping that of developing muscle cells, which extend filopodia to the axonal targeting of innervating motoneurons (Kohsaka and Nose, 2009;Ritzenthaler et al, 2000).…”
Section: Cell Recognition By Hbs-rst Interactionmentioning
confidence: 93%
“…Hbs might be preferentially localized at the protrusions of pLPCs that interact with R axons. The behavior of pLPCs is analogous to 3311 RESEARCH ARTICLE Hibris/Roughest in retinotopic mapping that of developing muscle cells, which extend filopodia to the axonal targeting of innervating motoneurons (Kohsaka and Nose, 2009;Ritzenthaler et al, 2000).…”
Section: Cell Recognition By Hbs-rst Interactionmentioning
confidence: 93%
“…Caps and its paralog Tartan (Trn) have extracellular domains containing leucine-rich repeats (LRR) and contribute partially redundant functions to the formation of compartment boundaries of the wing disc (27). caps mutants do not mediate selection of synaptic partners normally (2831), and Caps protein localizes at filopodia tips during partner recognition and synapse stabilization (29). We observed similar types of effects on ASP cytonemes.…”
Section: Dpp Signaling In the Asp Requires Cytoneme-mediated Transportmentioning
confidence: 99%
“…In recent years, several Drosophila LRR proteins were demonstrated to affect targeting of motor axons and of specific muscles (Kohsaka and Nose, 2009;Kurusu et al, 2008). Intriguingly, simultaneous labeling of the presynaptic and postsynaptic sites showed that, before synapse formation, muscle membrane extensions called myopodia express the LRR protein Capricious at their tips (Kohsaka and Nose, 2009). These myopodia tips interact with axonal tips in order to form a properly located synapse.…”
Section: Research Articlementioning
confidence: 99%
“…Mutants in these genes exhibit a wide range of phenotypes, depending on their tissuespecific distribution. However, they share a common function in cell-cell recognition events (Blair, 2001;Kohsaka and Nose, 2009;Krause et al, 2006;Milan et al, 2002;Milan et al, 2005;Milan et al, 2001;Sakurai et al, 2007). Two additional LRR proteins, Haf and CG8561 (Convoluted -FlyBase), expressed by muscle cells, affect motor axon recognition of specific muscles (Kurusu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%